2020
DOI: 10.1021/acs.orglett.9b04567
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Diels–Alder Cycloaddition/Cross-Coupling Sequences of 2-Bromo-1,3-butadienes

Abstract: 2-Bromo-1,3-butadienes are demonstrated to be effective substrates for tandem Diels–Alder/transition metal cross-coupling reaction sequences. Intermolecular cycloaddition of a 2-bromo-1,3-diene with activated dienophiles proceeded under Lewis acid catalysis in generally high yields with good to excellent endo diastereoselectivity. The resulting vinyl bromide cycloadducts underwent subsequent Stille and Suzuki cross-couplings under standard conditions in good yields. Both the Diels–Alder and cross-coupling step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…21 Meanwhile, the most recent study from our group in 2019 has demonstrated 2-bromo-1,3-butadiene systems (e.g., 103, Scheme 17) as highly effective substrates for tandem Diels-Alder-transition-metal cross-coupling reaction sequences. 58 Intermolecular cycloaddition of 2-bromodiene 103 with a variety of activated dienophiles was shown to proceed in generally high yield, with good to excellent endo diastereoselectivity. The resulting vinyl bromide cycloadducts 104 readily underwent subsequent Stille and Suzuki cross-couplings under standard conditions to provide access to novel substituted cyclohexene products 105.…”
Section: Recent Efforts Towards the 56-spirocyclic Imine Marine Toxin Portimine Amentioning
confidence: 99%
See 1 more Smart Citation
“…21 Meanwhile, the most recent study from our group in 2019 has demonstrated 2-bromo-1,3-butadiene systems (e.g., 103, Scheme 17) as highly effective substrates for tandem Diels-Alder-transition-metal cross-coupling reaction sequences. 58 Intermolecular cycloaddition of 2-bromodiene 103 with a variety of activated dienophiles was shown to proceed in generally high yield, with good to excellent endo diastereoselectivity. The resulting vinyl bromide cycloadducts 104 readily underwent subsequent Stille and Suzuki cross-couplings under standard conditions to provide access to novel substituted cyclohexene products 105.…”
Section: Recent Efforts Towards the 56-spirocyclic Imine Marine Toxin Portimine Amentioning
confidence: 99%
“…Scheme 17 Use of 2-bromodiene 103 in Diels-Alder cycloadditions to access 5,6-spirocyclic imine 106 by Brimble and Furkert et al58 …”
mentioning
confidence: 99%
“…Brimble, Furkert, and co‐workers recently described such stepwise reactions starting with Lewis acid catalysed cycloaddition of the 2‐bromo‐1,3‐butadiene 1 using BF 3 ⋅ Et 2 O (Scheme 2). [11] After workup and isolation, the brominated cycloaddition products were then functionalized with Stille and Suzuki cross‐coupling reactions using 10 mol% Pd(PPh 3 ) 4 . Depending on the dienophile, some of the cycloaddition reactions required heating to 60 °C, the use of neat BF 3 ⋅ Et 2 O, and/or other Lewis acid catalysts like neat TiCl 4 to afford the cycloaddition products in good yields and at reasonable timescales [11] .…”
Section: Resultsmentioning
confidence: 99%
“… [11] After workup and isolation, the brominated cycloaddition products were then functionalized with Stille and Suzuki cross‐coupling reactions using 10 mol% Pd(PPh 3 ) 4 . Depending on the dienophile, some of the cycloaddition reactions required heating to 60 °C, the use of neat BF 3 ⋅ Et 2 O, and/or other Lewis acid catalysts like neat TiCl 4 to afford the cycloaddition products in good yields and at reasonable timescales [11] . The more forcing catalysis conditions required for cycloaddition reactions to occur with 1 made them ideal candidates for challenging the reactivity of ligand‐centered borenium ions generated in ( R TBDPhos)PdCl 2 complexes.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, iododienes are interesting species for organic chemistry because of their wide reactivity. These compounds are precursors in Diels-Alder reactions [4], palladium-catalyzed reactions [5] such as Stille [6], Negishi [7], and Sonogashira [8] and carbonylation cross-couplings [9], solvolysis [10] and metalation reactions [11].…”
Section: Introductionmentioning
confidence: 99%